Analisis Pengaruh Nilai Tukar, Jumlah Uang Beredar, dan Cadangan Devisa Terhadap Ekspor Migas di Indonesia - Wibiyantoro, Danang; Fatimah, Atika; Anggrismono, Anggrismono (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to investigate the impact of exchange rates, money supply, and foreign exchange reserves on oil and gas exports in Indonesia. The research adopts a quantitative approach, using time series data from 2005 to 2022. The method employed is the Error Correction Model with Eviews 12. The tests conducted include unit root tests, cointegration tests, the Error Correction Model involving long-term and short-term tests, and classical assumption tests. The results of the analysis reveal that, in the long term, the exchange rate does not significantly affect oil and gas exports in Indonesia, whereas both the money supply and foreign exchange reserves have a significant impact on oil and gas exports. In the short term, neither the exchange rate nor the money supply significantly influence oil and gas exports, while foreign exchange reserves have a significant impact on oil and gas exports in Indonesia.